The effect of an animation movie for inpatient fall prevention: a pilot study in an acute hospital. Issue 1 (December 2016) - Nakagami-Yamaguchi, Etsuko; Fujinaga, Kumiko; Batard, Akiko; Baba, Norio; Nakamura, Kazunori; Miyazaki, Kyoko; Mukai, Mayumi; Sugiura, Mikio; Nakatani, Tatsuya
Abstract Background In this study, we developed an animated movie as a novel educational tool for fall prevention, and intended for patients and caregivers. We evaluated this new animation, comparing its effectiveness both before and after intervention, and have discussed its potential in the context of inpatient fall prevention. Methods While including previously implemented multidisciplinary fall prevention measures, we started to introduce the use of animation in August 2013. Pre-and post-intervention questionnaire surveys were conducted for patients and nurses in June and August 2013, respectively, for 2 weeks. Results We obtained 304 and 269 paired data in the pre-and post- intervention survey periods. On examining the difference between nurses' instructions and patients' understanding, in the pre-intervention period, only 70.0 % of patients instructed to call the nurses at any time and 33.3 % of those instructed to call at the time of need, correctly understood the instructions. The frequency of patients' falls significantly decreased from 15.6 to 8.6 % (p <0.05) between the pre- and post- intervention survey periods, respectively. In 65-year-old patients, the ratio of frequency significantly decreased from 19.0 to 7.6 % (p <0.01); however, it did not change in patients aged <65 years. Conclusions Our study indicated that animation could be an effective educational tool for inpatient fall prevention, even in older patients. In order to develop a multimedia tool with optimal educational impact, several aspects should be explored, including the addition of previous multidisciplinary approaches, increased variety of story and character design, improved hospital culture for better staff compliance and enhanced effectiveness, and interactive digital media content for an effective teaching feedback loop.